Research of New Generation 3D Printer - Hajiyeva, K.R. (Herald of Azerbaijan Engineering Academy, 2021)
In the article, a new generation 3D printer is designed to improve the technological performance based on the analysis of 3Dprinter design principles, and it is proposed to prepare a software-controlled stabilization system, by studying the features of the optimal stabilization system for hastiness. The issues of research and synthesis of the control system of the working body of the 3D printer were considered, and at the same time the optimal control algorithm was developed.